Innovative Theories in Education Bridging Tradition and Modern Learning Practices - Juliane Fostersti; Mateozare Sánchezen; Emiliana Taralloto; Jhonson Thomas Antique; Hassan, Hassan Ali Muhammed Ramdhan (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
Contemporary education faces the challenge of bridging a rich tradition of values with the fast-paced, technology-driven demands of modernity. This research aims to explore innovative theories in education that integrate traditional elements with modern learning practices. The study employs a library research method to gather data from various primary and secondary sources, including books, scholarly journals, and academic articles. The findings indicate that the integration of tradition and modernity in education can create a holistic approach that encompasses cognitive, affective, and moral aspects. The implementation of innovations such as technology-based learning and blended learning becomes more effective when accompanied by culturally relevant traditional values. However, challenges such as cultural resistance, infrastructure limitations, and the need for adequate teacher training remain. This study emphasizes the importance of flexible, value-based curriculum design to create inclusive and sustainable education. The findings have significant implications for the development of educational policies that can address global challenges while maintaining local identity.